2013
DOI: 10.1002/hep.26573
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor-4α reverses malignancy of hepatocellular carcinoma through regulating miR-134 in the DLK1-DIO3 region

Abstract: Hepatocyte nuclear factor-4a (HNF4a) is a dominant transcriptional regulator of hepatocyte differentiation and hepatocellular carcinogenesis. There is striking suppression of hepatocellular carcinoma (HCC) by HNF4a, although the mechanisms by which HNF4a reverses HCC malignancy are largely unknown. Herein, we demonstrate that HNF4a administration to HCC cells resulted in elevated levels of 28 mature microRNAs (miRNAs) from the miR-379-656 cluster, which is located in the delta-like 1 homolog (DLK1) -iodothyron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 44 publications
3
82
2
Order By: Relevance
“…Yin et al (2013) confirmed decreased miRNA-134 expression in HCC tissues and its association with more aggressive pathological features, including liver cirrhosis, high levels of α-fetoprotein, large tumor size, advanced tumor stage, presence of tumor microsatellites, and absence of tumor encapsulation (Yin et al, 2013). Overexpression of miR-134 in HCC cells arrested cell growth and decreased cell migration and invasion by downregulating the oncoprotein KRAS.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Yin et al (2013) confirmed decreased miRNA-134 expression in HCC tissues and its association with more aggressive pathological features, including liver cirrhosis, high levels of α-fetoprotein, large tumor size, advanced tumor stage, presence of tumor microsatellites, and absence of tumor encapsulation (Yin et al, 2013). Overexpression of miR-134 in HCC cells arrested cell growth and decreased cell migration and invasion by downregulating the oncoprotein KRAS.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, miR-134 has been implicated in the pathogenesis of several types of tumors and plays dual roles in different tumors. It is significantly increased in head and neck squamous-cell carcinoma (HNSCC) and acts as a potential oncogene (Liu et al, 2014), while it is downregulated and acts as a candidate tumor suppressor in gastrointestinal stromal tumors (GISTs) (Haller et al, 2010), gliomas (Lages et al, 2011), non-small cell lung cancer (Li et al, 2012), hepatocellular carcinoma (Yin et al, 2013), and prostate cancer (Wang et al, 2011). However, very little is currently known about the links of miR-134 dysregulation to clinicopathological characteristics of osteosarcoma, and the functional attributes of miR-134 associated with osteosarcoma progression remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…miR-134 was first identified as a brain-specific miRNA located at 14q32 (25); it was observed to be localized in the synapto-dendritic compartment of hippocampal neurons and involved in the regulation of the neuronal microstructure (26). Previous studies have indicated that miR-134 was involved in several physiological and pathological processes; Han et al (27) identified that miR-134 has a crucial role in the translation-dependent guidance of nerve growth cones.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs play essential roles in diverse biological processes, including cell proliferation, differentiation, apoptosis, and tumor oncogenesis (4)(5)(6). Recently, numerous studies have revealed that miRNAs play critical roles in osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%